Pendekatan Maqasid Syariah dan Peran Keuangan Syariah untuk Mitigasi Dampak Ekonomi Pandemi Covid-19 - Mochammad Arif Budiman (Indonesian Journal of Applied Accounting and Finance, 2021)
The COVID-19 pandemic has had a serious and broad impact on the economies of all countries in the world. In this case, the government needs to respond appropriately and take various handling steps quickly to mitigate these various economic impacts so that economic resilience and the survival of all citizens in the midst of a pandemic situation can still be saved. Maqashid Syariah which emphasizes maintaining the safety of religion, mind, soul, lineage, and property can be used as an approach strategy in overcoming the Covid-19 pandemic. Islamic finance with its various instruments can also be optimized as an alternative to mitigating the economic impact of the pandemic.